2021
DOI: 10.4315/jfp-19-595
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Profile, Incidence, and Behavior of Salmonella on Seeds Traded in Mexican Markets

Abstract: Seed consumption has increased in recent years because the high nutrient content of seeds. However, the number of outbreaks caused by Salmonella associated with the consumption of low water activity food items has also increased, although these food items do not support microbial growth. The main goal of this study was to quantify microbial indicators and to determine the prevalence and content of Salmonella spp. in chia, amaranth and sesame seeds obtained from Mexican retail outlets. In addition, the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The seed samples recorded very low Aw values, ranging from 0.427 ± 0.024 (sample Q3) to 0.514 ± 0.024 (sample A3). Our results are similar to those reported by other authors for amaranth, chia, and sesame seeds [41].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The seed samples recorded very low Aw values, ranging from 0.427 ± 0.024 (sample Q3) to 0.514 ± 0.024 (sample A3). Our results are similar to those reported by other authors for amaranth, chia, and sesame seeds [41].…”
Section: Resultssupporting
confidence: 93%
“…Other authors also found yeasts and moulds with similar microbial load in different seeds from Mexico and Portugal [41]. Spore-forming bacteria were also found in spices from the United States (with values from 2.0 ×10 2 to 8.3 ×10 7 CFU/g) [48] and in Australian wheat (10 4 CFU/g) [49].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…For the food industry and regulatory organizations, the microbiological safety of tahini and its derivative products has increased in importance. However, Salmonella is a great hazard joined with sesame infection bacteria worldwide [ 46 ]. Tahini is thought to be shelf stable due to its low water activity; however, due to its high fat content, it may cause cross-protection against negative environmental factors, which might prolong the survival of pathogens such as Salmonella under different storage conditions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%